Nonasthmatic Chronic Cough: No Effect of Treatment with an Inhaled Corticosteriod in Patients without Sputum Eosinophilia - Marcia MM Pizzichini; Emilio Pizzichini; Krishnan Parameswaran; Lynda Clelland; Ann Efthimiadis; Jerry Dolovich; Frederick E Hargreave (Canadian Respiratory Journal)
BACKGROUND: Inhaled corticosteroids are effective in suppressing a chronic cough without asthma associated with sputum eosinophilia.